Numerical analyses of concrete thermal energy storage systems: effect of the modules' arrangement. (December 2020) - Doretti, Luca; Martelletto, Francesca; Mancin, Simone
Abstract: This paper is focused on modularized concrete sensible thermal energy storage systems with thermal oil as heat transfer fluid; the thermal storage systems have been conceived to be integrated into a concentrated solar power plant. This work is mainly focused on the effect of the modules' arrangement on the overall performance of the thermal energy storage system. Series and parallel arrangements are investigated, to determine the most performant solutions in terms of exchanged thermal energy as a function of the main operating conditions: oil mass flow rate and pressure drop, both in heating and cooling phase. Two different boundary conditions are considered: adiabatic and diabatic external walls. The simulations are carried out using an extended version of a model proposed by the present authors for a single concrete block, that was validated with experimental data. The exchanged thermal energy, the oil mass flow rate, the pressure drops, and the duration of the process are changed to evaluate the storages under different operating conditions. The best thermal energy storage configuration is determined by a thermal energy assessment: it coincides with the first one that reaches the asymptotic values with the minimum number of elements. Furthermore, in the diabatic case, the loss heat flux toward the environment has a significant role and highlights the differences between charging and discharging phases, its presence contributed to a more aware choice of the most suitable and performant modularized system. Highlights: Thermal storage concrete modules in series and parallel arrangements are investigated. The exchanged thermal energy is assessed both in the charging and discharging phase. In the diabatic case, the loss heat flux highlights the differences between charging and discharging phases.